Is Obesity a risk factor for increased Perioperative Blood loss following Laparotomy? A Matched Cohort Study from South Africa. - Gokal, Nishen; Gopalan, Pragasan Dean; Moodley, Yoshan (Student's Journal of Health Research Africa, 2022)
Background: The prevalence of obesity is growing in the South African (SA) population. Some of these obese individuals might require surgery during their lives. However, there are no specific studies from this setting that have investigated the impact of obesity on perioperative complications, such as blood loss, following high-risk abdominal surgery. This knowledge has potentially important implications for the perioperative management of obese SA abdominal surgery patients. Our objective was to address the identified gap in the published literature. Methods: We conducted a matched cohort study involving data from an existing laparotomy database at a SA tertiary hospital. Non-obese and obese patients were matched on established factors associated with perioperative blood loss. The Gross Equation was used to calculate the estimated perioperative blood loss. Mean estimated perioperative blood loss (with standard deviation - SD) was then statistically compared between obese and non-obese patient groups. Results: 58 patients were matched (29 non-obese and 29 obese). The estimated mean (SD) perioperative blood loss in non-obese patients was 806.96 (536.9) mL. The estimated mean (SD) perioperative blood loss in obese patients was 725.06 (513.9) mL. Overall, there was similar perioperative blood loss between non-obese and obese patients (p=0.438). Conclusion: Obese and non-obese patients undergoing laparotomy experienced similar blood loss. Recommendations: Obese patients in our setting should be managed for perioperative bleeding in the same way as non-obese patients.